KECEMASAN PADA PASIEN DIABETES MELITUS TIPE II BERDASARKAN LAMANYA SAKIT - Nonok Karlina (JURNAL KESEHATAN INDRA HUSADA, 2022)
Diabetes mellitus (DM) is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin produced. Someone who has diabetes mellitus is required to undergo several treatments, changes in lifestyle and regulation of food consumption. Changes in life can result in people with diabetes mellitus showing negative psychological reactions including anxiety. The purpose of this study was to determine the anxiety in patients with type II diabetes mellitus based on the duration of illness in the Internal Diseaase Room of Waled Hospital, Cirebon Regency. This type of research is descriptive quantitative with a retrospektif approach. The population in this study were all type II diabetes mellitus patients who were treated in the Internal Diseaase Room of Waled Hospital, Cirebon Regency in 2018 with 224 people and 69 people using the purposive sampling method. Data analysis was performed using univariate analysis with percentage. The results showed that more than a portion of respondents experienced moderate anxiety as many as 45 people (55.2%) and more than some respondents suffered from type II diabetes mellitus ≤ 5 years as many as 41 people (59.4%). It is expected that patients with type II diabetes mellitus can improve their ability to reduce their anxiety levels by doing positive things, such as attending dietary counseling for patients with type II diabetes mellitus